Diverse contributions of the visceral fat area to the etiology of two distinct subtypes of esophago-gastric junctional adenocarcinoma. (2nd December 2022) - Watanabe, Kenta; Koizumi, Shigeto; Shirane, Kenji; Tsuda, Hidehiko; Watanabe, Hiroyuki; Tsuji, Tsuyotoshi; Onochi, Kengo; Yamai, Kiyonori; Kusano, Chika; Dohmen, Takahiro; Horikawa, Yohei; Ajimine, Takuma; et al.
Abstract: Background: There are two distinct etiologies of esophago-gastric junctional adenocarcinomas (EGJACs): one associated with extensive gastric mucosal atrophy (GA), resembling non-cardiac gastric cancers; and the other related to gastro-esophageal reflux disease, resembling esophageal adenocarcinoma. In this study, we investigated the associations between the visceral fat area (VFA) and EGJACs separately in the two subtypes of EGJACs, depending on the extent of background GA. Methods: Sixty-four consecutive patients with EGJACs (Siewert type 2) were enrolled from a population-based database in Akita Prefecture, Japan, between 2014 and 2019. Two age- and sex-matched healthy controls were randomly assigned to each EGJAC case. The extents of GA were evaluated endoscopically, and the VFA values were measured based on computed tomography images. Logistic regression analyses were performed to investigate the associations between EGJACs and the VFA. Results: Study subjects were classified into 2 subgroups depending on the extent of endoscopic GA: 29 (45.3%) without and 35 (54.7%) with extensive GA. Multivariable regression analyses revealed that a VFA of ≥100 cm 2 was significantly associated with EGJACs in subjects without extensive GA [odds ratio (95% confidence interval): 2.65 (1.08–6.54)], while there was no such association in subjects with extensive GA [odds ratio (95% confidence interval): 1.52 (0.60–3.83)]. Conclusions: The contribution of the VFA to the etiology of EGJACs seems to differ depending on the extent of background GA, with the VFA more prominently associated with EGJACs in subjects without extensive GA than in those with it, providing further rationale concerning the heterogeneous nature of EGJAC etiology.